Negative theology and science in the thought of Semyon Frank - Obolewicz, Teresa (Studies in East European thought, 2010)
Semën Frank (1877-1950) considered the Universe as the “all-unity.” According to him, everything is a part of the all-unity, which has a divine character. God is present in the world, but his nature is incomprehensible. In this article I analyze two consequences of Frank’s panentheistic view of the relation between science and theology. Firstly, the limits of scientific knowledge allow recognition of the mystery of the world and the transcendence of God. Secondly, Frank claimed that nature is a “trace” of God and the manifestation of the absolute reality, i.e. the all-unity. As a result, both science and theology lead to the knowledge of God, although we cannot understand His essence.